FORMS OF ORGANIZATION OF PRACTICAL TRAININGS IN GEOGRAPHY CLASSES AND THEIR PURPOSE, TASKS AND IMPORTANCE - Abdimurotov Oybek Uralovich (Scholar Express Journal, 2021)
The article is based on the goals and objectives of practical training in geography, forms of practical training in natural geography and methods of its organization (lithosphere), features of the organization of practical training on natural geographical processes in the hydrosphere and atmosphere. directions for their implementation are described and the importance of practical training is indicated
Keywords: Geography; Natural Geography; Practical Training; Methodology